(untitled) (International Journal of Food and Nutritional Sciences, 2022)
The expansion of urban centers is being rapidly increasing, owing to huge population growth and migration toward urban centers, resulting in a lack of basic infrastructural facilities such as water supply, sanitation and sewerage, solid waste management and so on. The scrap dealers and rag pickers plays a vital role in the solid waste management practice. The rag pickers actually going through the dustbins and collecting rags, selling to the scrap dealers and earning the minimum wage sustain their daily needs converting wealth from waste, the scrap dealers were having their own shops and linkage with the recycling process. This two category of stakeholder’s are strengthening this recycling process. The scrap dealers were collecting waste from the households and also collecting from the rag pickers, the scrap dealers are selling the bulk of waste scrap’s to the agent of recycling industry and earning income. But the scrap dealers provide lesser wage to the rag pickers. This paper seek to address the entrepreneurial skill of scrap dealers and their working modality and profit from waste in Puducherry urban centers was discussed in this paper.